Ischemic Stroke Profile, Risk Factors, and Outcomes in India: The Indo-US Collaborative Stroke Project. Issue 1 (January 2018) - Sylaja, P.N.; Pandian, Jeyaraj Durai; Kaul, Subhash; Srivastava, M.V. Padma; Khurana, Dheeraj; Schwamm, Lee H.; Kesav, Praveen; Arora, Deepti; Pannu, Aman; Thankachan, Tijy K.; Singhal, Aneesh B.
Abstract : Background and Purpose—: The Indo-US Collaborative Stroke Project was designed to characterize ischemic stroke across 5 high-volume academic tertiary hospitals in India. Methods—: From January 2012 to August 2014, research coordinators and physician coinvestigators prospectively collected data on 2066 patients with ischemic stroke admitted <2 weeks after onset. Investigator training and supervision and data monitoring were conducted by the US site (Massachusetts General Hospital, Boston). Results—: The mean age was 58.3±14.7 years, 67.2% men. The median admission National Institutes of Health Stroke Scale score was 10 (interquartile range, 5–15) and 24.5% had National Institutes of Health Stroke Scale ≥16. Hypertension (60.8%), diabetes mellitus (35.7%), and tobacco use (32.2%, including bidi/smokeless tobacco) were common risk factors. Only 4% had atrial fibrillation. All patients underwent computed tomography or magnetic resonance imaging; 81% had cerebrovascular imaging. Stroke etiologic subtypes were large artery (29.9%), cardiac (24.9%), small artery (14.2%), other definite (3.4%), and undetermined (27.6%, including 6.7% with incomplete evaluation). Intravenous or intra-arterial thrombolysis was administered in 13%. In-hospital mortality was 7.9%, and 48% achieved modified Rankin Scale score 0 to 2 at 90 days. On multivariate analysis, diabetes mellitus predicted poor 3-month outcome and younger age, lower admission National Institutes of Health Stroke Scale and small-artery etiology predicted excellent 3-month outcome. Conclusions—: These comprehensive and novel clinical imaging data will prove useful in refining stroke guidelines and advancing stroke care in India.